KESALAHAN BERBAHASA DALAM KARANGAN DESKRIPSI SISWA SEKOLAH DASAR - Suryati Suryati (EDU-KATA, 2020)
The aim of this research was to describe the Speak Errors in Desciptive Essay of Fifth Grade Students of Elementary School. The data of this research was Desciptive Essay of Fifth Grade Students SDN Pengangsalan II Kalitengah Lamongan. To collect the data, this research used three techniques, namely : documentation technique, refer technique, and noted technique. The result of this research there are some errors, which include : spelling errors, namely : capital letter usage errors, punctuation usage errors, it consists of dot usage errors and comma usage errors, repetition words writing errors, preposition writing errors, conjunction usage errors, and adverb of cause writing errors. Besides that, there are diction errors namely : synonim words usage error, conjunctive pairs usage error, and task word usage error. There are some sentence structure errors, namely : carelessness of words usage, incoherence, and indiscretion of words usage.